1993
DOI: 10.1111/j.1600-0714.1993.tb01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus: a virus of increasing relevance to oral medicine and pathology

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous herpesvirus, emerging as an opportunistic pathogen in immunocompromised persons, particularly those infected with human immunodeficiency viruses (HIV). Clinical syndromes caused by HCMV are usually not specifically identifiable without laboratory investigations. However, it is now apparent that HCMV may cause oral ulceration in immunocompromised persons and it may play a role in other diverse conditions in these and other patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…20,87 There are suggestions that chronically elevated basal endogenous glucocorticoid levels, even at concentrations that might appear within the physiologic range as observed in the impoverished children (Table 3), promote a shift from a type 1 to a type 2 cytokine production profile. 88,89 Glucocorticoid excess enhances replication of a number of latent viruses, [90][91][92] and promotes increased susceptibility of the oral mucosa to viral infections. 91 Increased steroid levels in the mouth could also serve as a rich nutrient source for anaerobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,87 There are suggestions that chronically elevated basal endogenous glucocorticoid levels, even at concentrations that might appear within the physiologic range as observed in the impoverished children (Table 3), promote a shift from a type 1 to a type 2 cytokine production profile. 88,89 Glucocorticoid excess enhances replication of a number of latent viruses, [90][91][92] and promotes increased susceptibility of the oral mucosa to viral infections. 91 Increased steroid levels in the mouth could also serve as a rich nutrient source for anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…88,89 Glucocorticoid excess enhances replication of a number of latent viruses, [90][91][92] and promotes increased susceptibility of the oral mucosa to viral infections. 91 Increased steroid levels in the mouth could also serve as a rich nutrient source for anaerobes. 20 Stress also impairs salivary gland function, reducing the volume of saliva and the availability of salivary proteins, which are protective against the growth and pathogenicity of oral microflora.…”
Section: Discussionmentioning
confidence: 99%
“…After the primary infection, which is usually subclinical and occurs at an early age, HCMV infection is thought to persist for the life of the host [Weller, 1971]. A number of reports have suggested that the virus may persist in a wide variety of cells, including lymphocytes, monocytes, and cells of the oropharynx, kidneys, lungs, liver, blood vessels, reproductive organs, and/or various secretory glands [Roche et al, 1981;Rice et al, 1984;Dudding and Garnett, 1987;Grundy, 1990;Mocarski et al, 1990;Nelson et al, 1990;Epstein and Scully, 1993;Kowalik et al, 1994]. Particularly germane to the possibility that HCMV may be involved in affecting the sensitivity to tobacco carcinogens are a series of reports from our laboratory and others indicating that HCMV infection in vitro induces genetic alterations and potentiates the genotoxic effects of some chemicals.…”
Section: Introductionmentioning
confidence: 98%
“…Some infections, parti-cularly gram-negative, viral and fungal infections, are more frequent and severe in glucocorticoid-treated patients (Dale and Petersdorf, 1973). Glucocorticoid excess enhances replication of a number of latent viruses (Scully and Porter, 1994;Glaser et al, 1994), promotes increased susceptibility of the oral mucosa to viral infections (Epstein and Scully, 1993) and promotes a shift from a Type 1 to a Type 2 cytokine production profile (Clerici and Shearer, 1993).…”
Section: Discussion Of Proposed Pathogenesis Of Nomamentioning
confidence: 99%